2021
DOI: 10.3390/genes12121933
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the “Hot Phase” of a Familiar Left-Dominant Arrhythmogenic Cardiomyopathy

Abstract: We describe the case of a young man with an initial diagnosis of acute myocarditis that was finally recognized as a familial left-dominant arrhythmogenic cardiomyopathy. The diagnostic process was also based on demonstration, serial cardiac magnetic resonance imaging, and typical patterns of myocardial damage, including features of the disease’s inflammatory “hot phase”.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The full-text screening of these articles led to the exclusion of 56 studies due to their compliance with the inclusion/ exclusion criteria. The remaining 31 articles were considered eligible for this review [ 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] A PRISMA flow diagram depicts the flow of information through the different literature review phases ( Figure 1 ). Our inclusion criteria, with regard to the presence of detailed patients’ clinical features, led to the exclusion of several publications reporting a significant number of subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The full-text screening of these articles led to the exclusion of 56 studies due to their compliance with the inclusion/ exclusion criteria. The remaining 31 articles were considered eligible for this review [ 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] A PRISMA flow diagram depicts the flow of information through the different literature review phases ( Figure 1 ). Our inclusion criteria, with regard to the presence of detailed patients’ clinical features, led to the exclusion of several publications reporting a significant number of subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Native T1 mapping and extra-cellular volume (ECV) quantification are CMR sequences able to detect an increase in the interstitial space. It has been observed that native T1 values are higher in genotype-positive ACM patients than in the controls, probably related to the LV fibrosis observed in these individuals [ 23 ].…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%
“…Furthermore, it has been postulated that the timing of an EMB could be crucial for the detection of inflammatory infiltrates, which typically may alternate the “hot phases” of active inflammation and remission [ 23 ]. Therefore, an 18-FDG PET may unveil myocardial inflammation in cases being undetected in CMR scans, particularly when the concomitant troponin elevation is identified or in the case of chest pains.…”
Section: Cardiac Nuclear Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the cutaneous features, patients have been reported to have episodes of myocardial inflammation, sometimes provoked by exercise ( 18 , 19 ). These inflammatory episodes might be confused with myocarditis of other etiologies, which might delay diagnosis ( 20 , 21 ). Cardiac magnetic resonance imaging (CMR) may help in differential diagnosis ( 22 ).…”
Section: Introductionmentioning
confidence: 99%